2015
DOI: 10.1007/s11274-015-1910-6
|View full text |Cite
|
Sign up to set email alerts
|

An endophyte of Picrorhiza kurroa Royle ex. Benth, producing menthol, phenylethyl alcohol and 3-hydroxypropionic acid, and other volatile organic compounds

Abstract: An endophytic fungus, PR4 was found in nature associated with the rhizome of Picrorhiza kurroa, a high altitude medicinal plant of Kashmir Himalayas. The fungus was found to inhibit the growth of several phyto-pathogens by virtue of its volatile organic compounds (VOCs). Molecular phylogeny, based on its ITS1-5.8S-ITS2 ribosomal gene sequence, revealed the identity of the fungus as Phomopsis/Diaporthe sp. This endophyte was found to produce a unique array of VOCs, particularly, menthol, phenylethyl alcohol, (+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…This investigation showed that VOCs produced by the endophytic D apiculatum FPYF 3052 were able to inhibit the growth of fungal pathogens (Table 2). This result was consistent with evidence on the VOCs of some endophytic fungi of Diaporthe previously reported [7,14,15,17]. These fungi were recorded as Diaporthe sp.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This investigation showed that VOCs produced by the endophytic D apiculatum FPYF 3052 were able to inhibit the growth of fungal pathogens (Table 2). This result was consistent with evidence on the VOCs of some endophytic fungi of Diaporthe previously reported [7,14,15,17]. These fungi were recorded as Diaporthe sp.…”
Section: Discussionsupporting
confidence: 92%
“…The VOCs of Diaporthe sp. PR4 exhibited the greatest inhibition rate on Rhizoctonia solani by 100% after 24 hours [14]. The VOCs of Diaporthe sp.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the previous research, geraniol has been detected as an important component in the aroma matrix of orthodox tea . Except that, citronellol and phenylethyl alcohol could also be used to enhance the fragrance and produce perfumes, and citronellol was detected as the main fragrance compound of rose scent from tree peony cultivars . On the contrary, there was a negative correlation between sweet attribute and benzaldehyde (−0.681), caused by bitter and almond scents of benzaldehyde .…”
Section: Resultsmentioning
confidence: 94%